2015
DOI: 10.3389/fped.2015.00062
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Postpartum Depressive Symptoms in Mothers and Fathers and Its Relation to Midwives’ Evaluation and Service Provision: A Community-Based Study

Abstract: BackgroundPostpartum parental mental health problems pose a serious risk for child development and often remain undetected in postpartum primary care. Within the framework of the German Midwifes Prevention Study, the aim of this study was to investigate the presence of postpartum emotional distress in mothers and fathers, and the detection of distressed parents by midwives in a primary care setting. We also examined whether a temporal extension of the postpartum midwife care period is associated with greater u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The use of screening tools were less likely during the early postnatal period where there was a reliance on clinical judgement and this may result in midwives not enquiring appropriately about the woman's psychosocial wellbeing and limiting the opportunity to identify women at risk of PMHPs (Yelland et al, 2007). When no systematic identification strategy is in use Anding et al, (2015) found that based on ratings midwives only identified half of mothers with high EPDS scores and who reported significant postnatal depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The use of screening tools were less likely during the early postnatal period where there was a reliance on clinical judgement and this may result in midwives not enquiring appropriately about the woman's psychosocial wellbeing and limiting the opportunity to identify women at risk of PMHPs (Yelland et al, 2007). When no systematic identification strategy is in use Anding et al, (2015) found that based on ratings midwives only identified half of mothers with high EPDS scores and who reported significant postnatal depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The potential implication of relying on selective screening is that women without an obvious presentation will be missed. Similarly, relying only on personal judgement may also result in those with significant risk factors, including those with a history of mental health problems not receiving the support required in the perinatal period (Anding, Röhrle, Grieshop, Schücking, & Christiansen, ; Heneghan, Morton, & DeLeone, ). There is no doubt that the practice of exclusion or selective screening is a reflection of PHNs’ self‐reported lack of knowledge and skill in perinatal mental health compounded by a lack of education and organisational practice guidelines (Higgins et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In recognition of the gravity of mental health issues in childbearing women, professional organizations (National Institute for Health and Care Excellence, 2014) and researchers (Siu et al, 2016) have recommended routine screening to identify women at risk of mental health problems for early intervention. However, empirical evidence suggests that most childbearing women at risk of mental health problems are undetected, undiagnosed and untreated (Anding, Röhrle, Grieshop, Schücking, & Christiansen, 2015;Bayrampour et al, 2017;Fonseca, Gorayeb, & Canavarro, 2015). This observation provides the impetus for studies to explicate factors that can be improved to promote mental and emotional well-being in this vulnerable population.…”
Section: Introductionmentioning
confidence: 99%